Effects of hydrological changes on cooperation in transnational catchments: the case of the Syr Darya. Issue 7 (3rd October 2017) - Bocchiola, D.; Pelosi, M. G.; Soncini, A.
ABSTRACT: Water allocation along the Syr Darya River may be affected by climate change. Here we statistically model cooperation strategies, country profits, and sensitivity of cooperation, showing that the hydrological regime affects transboundary cooperation. Climate change in the twenty-first century may reduce glacial cover, and reducing stream flows, decreasing chances of cooperation and potentially raising conflicts. Comparison with other transboundary catchments in Central Asia indicates moderate-to-high risk of conflicts for the Syr Darya. A template is provided for assessment of the stability of cooperation in the Syr Darya basin, and in catchments similarly dependent on water availability.